Relokasi Mandiri Permukiman Desa Gurukinayan Akibat Kejadian Erupsi Gunung Api Sinabung Kabupaten Karo - Manurung, Rudi Kristian; Trimurni, Februati (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2020)
Gurukinayan Village is being relocated because this village is located in the Disaster Prone Areas Region (KRB) III. Gurukinayan Village was relocated to a safer place so that the community could have a decent life. Relocation has been slow due to government support still low, both political and administrative support. This research identifies the community's opinion on the relocation of settlements, analyzes the location of the relocation destination and examines what happens in the settlement relocation plan. Bardach states there are criteria for looking at independent relocation in the village of Gurukinayan, these criteria complement legaly, political acceptance, and robustness in conditions of administrative implementation, and improvability. The method used is a qualitative research method. Research data obtained through observation and interviews, also includes literature review and data from government organizations that require independent relocation. Based on the research results, in the eradication of the Mount Sinabung eruption disaster, there have been recommendations for the design of financial problems policies and the availability of ready-made funds that can be accessed by the Karo Regency BPBD. However, efforts to improve policies to create alternative solutions have not yet arrived at plans to make preparations for effective improvement of the eruption of the Mount Sinabung disaster. The results of this study offer a new concept, namely the discussion of the implementation of the Sinabung eruption disaster management policy must be supported by the community, protection, and professional organizational capabilities so as to be able to support access to law and political policy and support resilience in conditions of administrative implementation and improvability.